Cultural Understanding Level of Internship Students Japanese Language Learners at the Elementary and Intermediate Level - Lispridona Diner; Rina Supriatnaningsih; Lisda Nurjaleka; Yoshiro Nabeshima (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
Cross-cultural understanding is a crucial competency for students participating in international internship programs, particularly in Japan, which is known for its distinctive work norms and social values. This study aims to analyze the cultural understanding levels of students from the Japanese Language Education Program at Universitas Negeri Semarang who joined internships in Japan in 2023 and 2024. The data were collected through questionnaires distributed to 25 participating students. The results reveal that students' understanding of general culture was 24%, Japanese work culture 64%, and cultural aspects in Japanese communication 76%. The highest comprehension was in dining culture (92%), while the lowest was in workplace discipline (16%). These findings suggest a gap in students’ understanding of both general and work-specific Japanese culture. Theoretically, this study contributes to the discourse on the need to integrate Japanese work culture education into university curricula, thereby holistically preparing students for the cultural challenges they will encounter in the Japanese workplace environment.